(untitled) (Al-Aasar, 2025)
Access to safe and clean drinking water is a critical challenge faced by humanity in the modern era. Water pollution caused by industrial waste, agricultural chemicals, and urban expansion has contaminated rivers, lakes, and groundwater, creating severe health hazards. Traditional purification methods such as boiling and sand filtration are limited in their ability to remove dissolved chemicals, heavy metals, and microplastics. This study focuses on electrically-based water purification techniques as an effective solution to water purification (Tathir-e-Aab). Methods such as Reverse Osmosis (RO), Ultraviolet (UV) sterilization, Electrodialysis, and Capacitive Deionization utilize electrical energy to remove physical, chemical, and biological contaminants from water. RO uses semi-permeable membranes to filter dissolved salts and fine particles, while UV sterilization destroys the DNA of microorganisms. Electrodialysis and capacitive methods exploit ion exchange and electric charge principles to purify water efficiently. The research also evaluates the Islamic jurisprudential perspective, determining whether water purified by these methods qualifies as "Mā’ Mutlaq" for ablution, bathing, and ritual use. Additionally, it considers issues like water wastage in RO systems and the use of membranes, assessing them against Islamic prohibitions on waste and impurity. By integrating classical fiqh principles with modern scientific techniques, this study provides a comprehensive analysis of water purification, offering both technological and religiously compliant solutions to water scarcity, contamination, and safe usage in contemporary societies.